2021
DOI: 10.3171/2021.1.focus201026
|View full text |Cite
|
Sign up to set email alerts
|

The need for overcorrection: evaluation of computer-assisted, virtually planned, fronto-orbital advancement using postoperative 3D photography

Abstract: OBJECTIVE The main indication for craniofacial remodeling of craniosynostosis is to correct the deformity, but potential increased intracranial pressure resulting in neurocognitive damage and neuropsychological disadvantages cannot be neglected. The relapse rate after fronto-orbital advancement (FOA) seems to be high; however, to date, objective measurement techniques do not exist. The aim of this study was to quantify the outcome of FOA using computer-assisted design (CAD) and computer-assisted manufacturing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…22 The individual case studies each described a patient with a frontoethmoidal meningoencephalocele, 23 a complex craniofacial cleft with hypertelorism, 24 an orbital fracture, 25 and a cranial intraosseous lipoma. 26 3DP was used in preoperative planning with the creation of mock surgical models in 2 studies, 23,24 used to create custom intraoperative cutting guides or molds in 6 studies, [20][21][22][24][25][26] and used to create custom cranioplasty implants in 2 studies. 24,26 The specific technology and materials used in the 3DP process were described in most of the included studies (Supplemental Table 2, Supplemental Digital Content 2, http://links.lww.com/ SCS/F801).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 The individual case studies each described a patient with a frontoethmoidal meningoencephalocele, 23 a complex craniofacial cleft with hypertelorism, 24 an orbital fracture, 25 and a cranial intraosseous lipoma. 26 3DP was used in preoperative planning with the creation of mock surgical models in 2 studies, 23,24 used to create custom intraoperative cutting guides or molds in 6 studies, [20][21][22][24][25][26] and used to create custom cranioplasty implants in 2 studies. 24,26 The specific technology and materials used in the 3DP process were described in most of the included studies (Supplemental Table 2, Supplemental Digital Content 2, http://links.lww.com/ SCS/F801).…”
Section: Resultsmentioning
confidence: 99%
“…22 One study mentioned that the estimated cost savings due to reduced operating time was 10,800€ based on historical comparison. 24 Two studies mentioned that the use of 3DP reduced intraoperative blood loss, 20,23 with 1 study quoting an estimated 6% reduction in average blood loss compared with previously documented cases. 23 One case study felt that the use of 3D printed materials also led to a 14.2% reduction in overall hospital length of stay compared with cases in previous literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Median improvement in orbital dystopia was 87.5%, and three patients were overcompensated, with one (case 10) showing an even greater deviation than that measured preoperatively. Several studies indicate that overcorrection is desired to achieve better results at long-term follow-up 35–37 ; therefore, it will be interesting to evaluate how these residual deviations develop at the 3-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that overcorrection is desired to achieve better results at long-term follow-up [35][36][37] ; therefore, it will be interesting to evaluate how these residual deviations develop at the 3-year follow-up. Evaluation of the data suggested that FOD resulted in a slight undercorrection in the ODA, in which case a more pronounced distraction would be desirable.…”
Section: Plastic and Reconstructive Surgery • February 2024mentioning
confidence: 99%